Muscular strength, functional performances and injury risk in professional and junior elite soccer players - Lehance, C.; Binet, J.; Bury, T.; Croisier, J. L. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Muscle strength and anaerobic power of the lower extremities are neuromuscular variables that influence performance in many sports activities, including soccer. Despite frequent contradictions in the literature, it may be assumed that muscle strength and balance play a key role in targeted acute muscle injuries. The purpose of the present study was to provide and compare pre-season muscular strength and power profiles in professional and junior elite soccer players throughout the developmental years of 15-21. One original aspect of our study was that isokinetic data were considered alongside the past history of injury in these players. Fifty-seven elite and junior elite male soccer players were assigned to three groups: PRO, n=19; U-21, n=20 and U-17, n=18. Players benefited from knee flexor and extensor isokinetic testing consisting of concentric and eccentric exercises. A context of lingering muscle disorder was defined using statistically selected cut-offs. Functional performance was evaluated throughout a squat jump and 10 m sprint. The PRO group ran faster and jumped higher than the U-17 group (P<0.05). No significant difference in isokinetic muscle strength performance was observed between the three groups when considering normalized body mass parameters. Individual isokinetic profiles enabled the identification of 32/57 (56%) subjects presenting lower limb muscular imbalance. Thirty-six out of 57 players were identified as having sustained a previous major lower limb injury. Of these 36 players, 23 still showed significant muscular imbalance (64%). New trends in rational training could focus more on the risk of imbalance and implement antagonist strengthening aimed at injury prevention. Such an intervention would benefit not only athletes recovering from injury, but also uninjured players. An interdisciplinary approach involving trainers, a physical coach, and medical staff would be of interest to consider in implementing a prevention programme.